Bacterial genomic epidemiology with mixed samples. Issue 11 (15th November 2021) - Mäklin, Tommi; Kallonen, Teemu; Alanko, Jarno; Samuelsen, Ørjan; Hegstad, Kristin; Mäkinen, Veli; Corander, Jukka; Heinz, Eva; Honkela, Antti
Abstract : Genomic epidemiology is a tool for tracing transmission of pathogens based on whole-genome sequencing. We introduce the mGEMS pipeline for genomic epidemiology with plate sweeps representing mixed samples of a target pathogen, opening the possibility to sequence all colonies on selective plates with a single DNA extraction and sequencing step. The pipeline includes the novel mGEMS read binner for probabilistic assignments of sequencing reads, and the scalable pseudoaligner Themisto. We demonstrate the effectiveness of our approach using closely related samples in a nosocomial setting, obtaining results that are comparable to those based on single-colony picks. Our results lend firm support to more widespread consideration of genomic epidemiology with mixed infection samples.